2017
DOI: 10.1097/ajp.0000000000000506
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability to Psychopathology and Dimensions of Personality in Patients With Fibromyalgia

Abstract: Patients with FM have a high probability of anxious-depressive-type psychopathologic alterations. Their vulnerability to these conditions may be determined by personality traits. The SD character dimension may have implications for therapy, as low SD is associated with the presence of psychopathology and with a low capacity to cope with the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Going a little further, we think that it is even more relevant in FM patients, if we focus in the large differences showed in MCMI-III inventory. In fact, Garcia-Fontanals et al [41] found that 50% of patients with FM showed Dysthymia.…”
Section: Discussionmentioning
confidence: 99%
“…Going a little further, we think that it is even more relevant in FM patients, if we focus in the large differences showed in MCMI-III inventory. In fact, Garcia-Fontanals et al [41] found that 50% of patients with FM showed Dysthymia.…”
Section: Discussionmentioning
confidence: 99%
“…43 Central pain sensitization is one key domain in FMS. Furthermore, the psychopathological pro le of FMS patients may contribute to the symptoms of FMS 27 . The psychopathological pro le may, on the one hand, contribute to enhanced pain sensation while, on the other hand, chronic pain may give rise to anxiety, depression and stress.…”
Section: Discussionmentioning
confidence: 99%
“…Since self-reported pain pro les do not always match quantitative sensory testing (QST) parameters in FMS patients [24][25][26] the rst major objective of the current study was to investigate whether FMS-related pro les of QST parameters are associated with alterations of the fecal microbiome. Given that FMS is linked with several psychological disturbances 27 , the second major objective was to examine whether FMS-related changes in psychometric scores (depression, anxiety, stress) are coupled to changes in microbial composition. In this way we set out to obtain more speci c information on the relevance of the gut microbiome to the pathophysiology of FMS.…”
Section: Introductionmentioning
confidence: 99%
“…[166][167][168] Harm-avoidance in particular may be relevant given its reported association with deficient pain modulation 169 and with affective symptoms. 170 Perfectionism, type D personality, and alexithymia have also been associated with pain and other bodily symptoms as well as emotional distress and negative cognitive processes. 121,160,[171][172][173] In a study, members of our group have demonstrated that health professionals experienced in managing FM can distinguish patients from controls, as a group, based on single items of a personality profiling tool (NEO-PI-R).…”
Section: C) Temperament and Personalitymentioning
confidence: 99%